ANALISIS MOTIVASI MAHASISWA PROGRAM STUDI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN MEMANFAATKAN PERPUSTAKAAN STKIP NIAS SELATAN - Idarwati Bu’ulolo; Hemat Zagoto (Universitas Nias Raya, 2020)
This research was motivated by the motivation of students of the Civics Study Program to use the Nias Raya University library. The development or decline of a campus library is largely determined by the motivation of students in utilizing the library and also the services provided. Lack of motivation of students of the PPKn Study Program, Faculty of Teacher Training and Education in utilizing the existing library collections, even though in the library there are references according to their respective departments, not even references to those majors that exist, even general collection references and others are also available in the library and students who visit the library are less and when there are students who visit most of the final semester students and on average they only use special collections (thesis) only. This research was conducted using qualitative methods. The location of this research was carried out in the library of the University of Nias Raya. Data collection methods used are interviews, observation and documentation. The results showed that there was an increase in the motivation of students from the Civics Study Program to use the Nias Raya University library. So it can be concluded that students of the Civics Study Program utilize the Nias Raya University campus library as a learning resource. The suggestion offered by the researcher is that the addition of a collection of books that can support student achievement and learning skills should be further improved.